Expression of Hong Kong Directors in the Chinese Main-Melody Film: The Artistic Propaganda (Asian Journal of Social Science Studies, 2022)
By analysing the main-melody film works of Hong Kong directors and the understandings and attitudes of audiences in both mainland China and Hong Kong toward these films, it is hoped that this research will contribute to a deeper understanding of the particularity of Hong Kong people’s national identity. This would provide a significant opportunity to advance the understanding of Hong Kong’s status and value in contemporary China and the world. Furthermore, this study will offer some critical insights into the distribution of Hong Kong films in mainland China.